Biological activity, chemical profiling and molecular docking of tissue extracts of the sea snail Trochus erithreus - Khaled M. Zayed, Mosad A. Ghareeb, Mohamed R. Habib, Hanaa M. Abu El-Einin, Rasha E.M. Ali, Rasha M. Gad El-Karim, Rehab Sabour, Ahmed A. Hamed (Journal of Applied Pharmaceutical Science, 2023)
The biodiversity of marine mollusks, along with their worldwide availability and ease of harvesting, makes them an enticing subject for scientific research. Mollusks are frequently the target of pharmaceutical scientists who are searching for novel compounds to benefit the population. This study targets the investigation of the antioxidant, antibiofilm, antimicrobial, and cytotoxic activities of different solvent extracts of marine mollusk Trochus erithreus. The chemical constituents of the most promising extract and molecular docking analyses are also investigated. Results showed that ethyl alcohol extract had the highest phenolic content (213.90 ± 4.88 mg GAE/ g extract), total antioxidant activity (545.33 ± 4.02 mg AAE/ g extract), and antibacterial activity against Staphylococcus aureus (31.32 ± 1.49), while the acetone extract had the highest scavenging effect against 2,2-diphenyl-1-picryl-hydrazyl radical (IC50: 53.59 ± 1.71 μg/ml). The acetone extract also displayed pronounced antibacterial activity against Proteus vulgaris with an inhibition ratio of up to 67.93% and it had potent cytotoxic effects against both prostate (IC50: 1.666 ± 0.07 μg/ml) and human lung carcinoma cell lines (IC50: 12.04 ± 0.55 μg/ml). Gas chromatography-mass spectrometry investigation of the acetone extract resulted in the recognition of 45 compounds. Bisabolol oxide A (24.63%), (E)-α-farnesene (7.89%), and tricyclo[8.2.0.0(2,5)] dodeca-3,6,8,11-tetraene (5.41%) were detected as major components. The molecular docking study demonstrated strong binding scores and modes of interactions of several major compounds, inside the active binding sites of bacterial enzymes, thymidylate kinase, DNA gyrase B, and DNA topoisomerase IV/subunit Bs.